White matter hyperintensities in relation to cognition in HIV-infected men with sustained suppressed viral load on cART - Su,T; Wit,FW; Caan,MW; Schouten,J; Prins,M; Geurtsen,GJ; Cole,JH; Sharp,DJ; Richard,E; Reneman,L; Portegies,P; Reiss,P; et al. (AIDS, 2016)
OBJECTIVES: The objective of this study was to assess whether HIV-infected patients on long-term successful combination antiretroviral therapy (cART) have more extensive white matter hyperintensities (WMH) of presumed vascular origin compared with uninfected controls and whether these intensities are associated with cognitive impairment. Furthermore, we explored potential determinants of increased WMH loadin long-term suppressed HIV infection. DESIGN: A cross-sectional comparison of WMH in an observational cohort. METHODS: Clinical, cognitive and magnetic resonance imagingdata were collected from 103middle-aged, aviremic HIV-infected menon cART and 70 HIV-uninfected, otherwise similar controls. In the MRI data, WMH load was quantified by automated approaches and qualitatively reviewed by an experienced neuroradiologist using the Fazekas scale. RESULTS: HIV-infected men hadan increased WMHload. Among HIV-infected patients, increased WMH load was independently associated witholder age, higher diastolic blood pressure and D-dimer levels,and longer time spent with a CD4 count below 500cells/mm. HIV-associated cognitive deficits were associated with increased WMHload. CONCLUSIONS: WMHare more extensive and associated with cognitive deficitsin middle-aged,aviremic cART-treated HIV-infected men. The extent of WMH load wasassociated with both cardiovascular risk factors and past immune deficiency. Since cognitive impairment in these same patients is also associated with these risk factors, this may suggest that in the setting of HIV, WMH and cognitive deficits share a common etiology. This supports the importance of optimizing cardiovascular risk management, and early, effective treatment of HIVinfection.